THE DEVELOPMENT OF PLURICULTURAL COMPETENCE IN PRE-SERVICE PHILOLOGY STUDENTS THROUGH PROBLEM-BASED LEARNING - Rakhmatova E’zoza Otabek qizi (Modern American Journals, 2025)
This article explores the development of pluricultural competence among pre-service philology students through Problem-Based Learning (PBL). Drawing on theoretical foundations of plurilingual and intercultural education, it demonstrates that PBL promotes analytical reflection on cultural diversity, fosters empathy, and enhances students’ ability to mediate between linguistic and cultural systems. Through problem-solving, collaboration, and real-life simulations, learners develop tolerance, open-mindedness, and adaptive communication strategies. PBL situates learning in authentic socio-cultural contexts, enabling students to connect theoretical linguistic knowledge with practical intercultural experience. The research also emphasizes how integrating cultural problem scenarios strengthens critical thinking and self-regulation in multilingual settings. Findings suggest that PBL is an effective pedagogical tool for building pluricultural competence by encouraging autonomous learning, dialogue, and cross-cultural understanding core qualities for future philologists in an increasingly globalized world.
Keywords: Pluricultural competence, problem-based learning, pre-service philologists, interculturality, plurilingualism, reflection, tolerance, mediation.